Diels–alder reactions of alkyl 2H-azirine-3-carboxylates with furans - Alves, M. José (2001)
Methyl 2-(2,6-dichlorophenyl)-2H-azirine-3-carboxylate 1 and furan give the aziridine 2 by a Diels–Alder cycloaddition reaction. The hydrolysis of compound 2 leads to a dihydrofuranol 11 by cleavage of a C–N bond. X-Ray crystal structures of compounds 2 and 11 have been determined. Compound 2 reacts with alcohols in a similar way to give 2-alkoxy-2,5-dihydrofurans as mixtures of cis and trans isomers. The structures of these compounds have been determined from an X-ray crystal structure of one of the methyl ethers, the trans isomer 13. The reaction of the azirine 1 with 1,3-diphenylisobenzofuran leads to the formation of two isomeric 1 : 1 adducts that have been identified as the products of endo and exo cycloaddition, 3 and 4. The endo isomer 3 is converted into the exo isomer 4 by heat. Similar Diels–Alder reactions have been carried out between furans and benzyl 2H-azirine-3-carboxylate 6. Hydrolysis of the adduct 7 formed with furan again produces a dihydrofuranol 25 as the major product together with three minor products, two of which are 1-azabicyclo[4.1.0]hept-3-ene-2,5-diols 27 and 28 that result from C–O bond cleavage. Protection of the mixture of alcohols with TBS triflate gives the bis(TBS) ether 31 of the trans-1-azabicyclo[4.1.0]hept-3-ene-2,5-diol as the major product, showing that this ring system can be produced from the dihydrofuranol 25. The bis(TBS) ether 30 of the cis-2,5-diol is a minor product and its structure has been established by independent synthesis through a Diels–Alder reaction between the azirine 6 and 1,4-bis(tert-butyldimethylsilyloxy)butadiene 32.